Can the chlorhexidine gluconate solution potentiate the staining of polycrystalline ceramic brackets? - Catharina e Silva Monteiro Barros; Jose Guilherme Neves; Ana Paula Terossi de Godoi; Ana Rosa Costa; Mario Vedovello Filho; Heloisa Cristina Valdrighi (Universidade Estadual de Campinas, 2019)
Aim: The present study aimed to assess, in vitro, the effect of chlorhexidine on the potentiation of polycrystalline ceramic bracket staining. Methods: Seventy-two polycrystalline ceramic brackets of upper right central incisors were divided into six groups (n=12) according to immersion solution. The groups were G1 - distilled water (control); G2 - chlorhexidine; G3 - coffee; G4 - red wine; G5 - chlorhexidine associated with coffee; and G6 - chlorhexidine associated with red wine. The samples were analyzed by means of a spectrophotometer according to the CIEL*a*b* system, and color change (ΔE*) was calculated. The readings were performed at the following times: T0 - After package removal and T1 - After staining. The data were analyzed by Kruskal Wallis and t tests (p<0.05) at 5% significance level. Results: The total color variation (ΔE*) was greater in the group that received chlorhexidine associated with red wine (p<0.05) and lower in the groups that received distilled water. All other groups showed greater value variations when compared to G1 and G2. Group G6 showed a greater color change due to the potentiation of chlorhexidine with the dye substance. Conclusion: It is concluded that chlorhexidine potentiates the staining caused by red wine in polycrystalline ceramic brackets.